2022
DOI: 10.1177/0092055x221114688
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Lectures Behind: Using Community-Engaged Learning in Research Methods Classes to Teach about Sustainability

Abstract: This article explores the outcomes of using community-engaged learning in a sustainability-focused social sciences research course titled Methods of Social Research. The integrated components of the course were designed to teach students about the research process while addressing sustainability issues at Utah State University. Throughout the course, students learned how to collect, analyze, and interpret data; work in research teams; write a grant; and write and present a final research paper. Student sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a large-scale longitudinal study, Astin et al (2000) found that students who had engaged in service learning activities showed improvements in not just academic performance but also leadership skills, self-efficacy, and a strengthened commitment to activism. Similarly, Soyer et al (2022) found that students engaged in applied sustainability-related research activity emerged with a heightened sense of self-efficacy, a key aspect of empowered civic engagement. It should be noted here that a sense of personal efficacy in regard to political engagement does not necessarily mean optimism in regard to issue outcomes.…”
Section: Inspiring Engaged Citizenshipmentioning
confidence: 92%
See 1 more Smart Citation
“…In a large-scale longitudinal study, Astin et al (2000) found that students who had engaged in service learning activities showed improvements in not just academic performance but also leadership skills, self-efficacy, and a strengthened commitment to activism. Similarly, Soyer et al (2022) found that students engaged in applied sustainability-related research activity emerged with a heightened sense of self-efficacy, a key aspect of empowered civic engagement. It should be noted here that a sense of personal efficacy in regard to political engagement does not necessarily mean optimism in regard to issue outcomes.…”
Section: Inspiring Engaged Citizenshipmentioning
confidence: 92%
“…The literature is rich with examples for how to foster civic engagement through exercises that can be used inside or outside of the sociology classroom (Ghoshal 2019; Matto et al 2017; Meza Rios et al 2018; Miller, Miller, and Spoelstra 2021; Soyer et al 2022). In Teaching Civic Engagement across the Disciplines , Matto et al (2017) provide a hands-on guide to creating such opportunities for students.…”
Section: Inspiring Engaged Citizenshipmentioning
confidence: 99%